Маневренность ластоногих (Pinnipedia) - Мордвинов, Ю.Е. (Вестник зоологии, 1972)
On the basis of analysis of shooling materials, observations of free swimming Callorhinus ursinus L. and Pusa caspica Gmel. and experiments carried out with these species of Pinnipedia, with interior or exterior flippers being removed by turns, the role of each pair of extremities was determined in the moment of rectilinear advance molion in water, during turns in horizontal and vertical planes and motion stabilization. It is established that in the species under study and in Pagophoca groenlandica Erxl. from the While sea some morphological peculiarities of the organism increasing the manoeuvre-bility of swimming animals develop progressively with the age.